Considerations for plant selection in green roofs - Arabi, Roozbeh; Shahidan, Mohd Fairuz; Mohd Shariff, Mustafa Kamal; Ja'afar, Mohamad Fakri Zaky; Rakhshandehroo, Mehdi (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
It is the vegetation layer that creates the living skin on the rooftop in green roofs, controls the long-term effect of any green roof installation and provides a naturally evolving and changing roofscape. Therefore, plant layer is the most challenging and important element of green roofs. A successful green roof system needs a meticulous plant selection. Considering aesthetic values, different designs are available which incorporate various plant species, but the vegetative layer requires wise consideration in terms of the projected goals and existing conditions. Design goals of the roof define the plant selection process, whether the goals are linked to aesthetic values, performance, education or function. Like any landscape at ground level, vegetative layer that propagate primarily on a green roof may not continue to flourish in the long term as a result of fluctuation in climate and other critical factors. While, aesthetic values and ecological aspects are crucial criteria in roofscape, the selected plants must first be survivable. The plant selection process relies on the building structure, aesthetic values, micro-climate condition, existing maintenance and the condition of growing medium. Necessarily, green roof vegetation must be less nutrient-reliant and tougher than plant species currently found in ground level landscape. In this case Crassulacean acid metabolism (CAM) plants are suggested. In Overall, the best plants for green roofs environment are cold, heat, drought, wind, sun, disease and insect tolerant and preferably native plant species. Drought resistant, durable and low maintenance plant species are recommended for extensive green roofs; however, almost infinite plant selection is used for intensive green roofs.